Use of Satellites in Terms of the Principle of Exploration and Use of Space for Peaceful Purposes - Kerem Batır; Pervin Şeker (Public and Private International Law Bulletin)
Space is now a predominant area for technological development, and its importance is increasing. This area was initially dominated by military activities but has hosted numerous agents over time. The launch of the Sputnik I satellite on October 4, 1957, marked a turning point in space exploration. This event signaled the beginning of the Space Age as the major powers continued their race for space. Activities involving space have increased in momentum since that time. The protection and regulation of space have become important because of interstate competition. The approaches of space powers and historical events were effective in the legal regulations. Moreover, some universal and unchangeable principles have been defined in legal regulations. In this context, the principle of “exploration and use of outer space for peaceful purposes” is significant. This principle has been interpreted in various ways, depending on the perspectives of actors vis-à-vis space. The current scenario of diversified actors and the expanding and changing structures of space-related activities necessitates a reevaluation of this principle, whose structural ambiguity renders the legality of some space activities controversial. Satellites represent one of the oldest and most important application areas of the space industry and their use evinces visible transformations. The dual use of satellites creates uncertainty in the context of the stated principle. The current circumstances thus necessitate a reconsideration of the relationships between space applications and the principle of peaceful use. This study examines the dual-use nature of satellites, citing examples of the principle of exploration and use of space for peaceful purposes.